2022
DOI: 10.1088/1755-1315/1053/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Bornean Pygmy Elephant habitat usage of natural salt licks in Segaliud Lokan Forest Reserve

Abstract: Bornean pygmy elephant (Elephas maximus borneensis) is crucial in the forests ecosystem as it plays a vital role as a forest engineer. As such, it is crucial to conduct more research to contribute to the conservation of this species. This study examined the pygmy elephant usage of natural salt lick in Segaliud Lokan Forest Reserve (SLFR), also known as FMU19B. Salt lick is vital to maintain wildlife health. This study investigated the elephant’s visitation frequency and examined its activity pattern in the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Mojiol and Lim (2022) conducted research at the same study site and reported high visitation of Tembadau at C59 salt lick. Sompud et al (2022) reported that the salt lick at C59SL is also preferred by the Bornean pygmy elephant (Elephas maximus borneensis). They further suggested that the physical attributes of the salt lick, which is undulating flat and large in size compared to all four salt licks, attract wildlife to it.…”
Section: Discussionmentioning
confidence: 99%
“…Mojiol and Lim (2022) conducted research at the same study site and reported high visitation of Tembadau at C59 salt lick. Sompud et al (2022) reported that the salt lick at C59SL is also preferred by the Bornean pygmy elephant (Elephas maximus borneensis). They further suggested that the physical attributes of the salt lick, which is undulating flat and large in size compared to all four salt licks, attract wildlife to it.…”
Section: Discussionmentioning
confidence: 99%